Speech Discrimination as a Function of Age - Manimegalai R (Journal of All India Institute of Speech and Hearing, 1970)
Gerontologists believe that the aging  process begins even before  we are born. Though some recent studies (Bergmon, 1967) indicate that our sensitivity for puretones increases till  puberty and thereon there  is a slight decline especially around 4 KHz. In addition  to the progressive deterioration in the sensitivity for   puretones generally  atributed  to presbycusis, the gereatric patient also typically demonstrate a reduced abitlity to understand the spoken language.  This  problem seems to be compatible with the account of puretone hearing loss.